Systemic review on personnel selection from the perspective of the labor organization and the candidate - Nolazco Labajos, Fernando Alexis; Menacho Carhuamaca, Jaime David; Maita Díaz, David; Luque Málaga de Reátegui, Norma Máxima (Revista de Ciencias Sociales, 2023)
The selection of personnel from the perspective of the labor organization and the candidate predisposes the purpose of conferring to the institutional structure capable people who can meet the appropriate profile to perform a job position and fulfill their functions optimally and can contribute to the achievement of the objectives. objectives of an organizational entity. The aim of this article was to carry out an analysis, based on the review of scientific publications, that would allow, from a conceptual perspective, understand how both the organization and the candidates perceive the personnel selection process. The descriptors in this review were personnel selection, organization, candidates, and human talent management. For this purpose, scientific articles in the Redalyc, Research Gate, Third Millennium Management, Scielo and Dialnet databases were taken into account. All the publications previously went through inclusion and exclusion criteria, finally selecting 51 articles to carry out the review work. It was concluded that an optimal selection of personnel guarantees greater productivity and efficiency in the work, which supports the effort in organizations to carry out an exhaustive filter of their personnel, taking into account that eighty percent of failures in organizations are related to an inadequate selection process.